Quality assurance in mammography: College of Radiology Survey in Malaysia - Ho, E.L.M.; Ng, Kwan Hoong; Wong, Jeannie Hsiu Ding; Wang, H.B. (Malaysian Medical Association, 2006)
Malaysia's mammography QA practice was surveyed based on the Malaysian Ministry of Health and the American College of Radiology (ACR) requirements. Data on mammography unit, processor, image receptor, exposure factors, mean glandular dose (MGD), sensitometry, image quality and viewbox luminance were obtained. Mean developer temperature and cycle time were 34.1 +/- 1.8degreesC and 107.7 +/- 33.2 seconds. Mean base+fog level, speed index and contrast index were 0.20+/-0.01, 1.20+/-0.01 and 1.33+/-0.26 respectively. Eighty-six percent of the fifty centres passed the image quality test while 12.5% complied with ACR recommended viewbox luminance. Average MGD was 1.0+/-0.4 mGy. Malaysia is on the right track for QA but with room for total quality improvement.